(untitled) (Biological Sciences - PJSIR, 1996)
The essential oil ofCupressus sempervirens L. obtainedbyhydro-distillationof fruitsattwostages wasanalysed by GC & GC-MS. The main components of the fruits at two stages range from a-pinene (44.59 -54.62%), sabinenc (7.86-2.86%), Dl-carene (15.45-21.83%). a-terpinene (5.25-3.90%).4-terpineol (6.58-0.04%)andcedrol (1.02-1.35%) respectively.